The Role of Modern Oratory in the Formation of Youth’s Spirituality - Nilufar Babajonova, Qodirova Moxinur Nodir qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article explores the essence of modern oratory, its communicative and educational functions, and its impact on shaping the spirituality and worldview of young people. In the context of globalization, the power of persuasive and culturally rich speech is becoming increasingly vital in developing patriotism, social activity, and moral consciousness among youth. The paper also analyzes the role of oratory in education, leadership, and media, while proposing practical approaches for integrating oratory training into modern curricula.